2017
DOI: 10.1177/1078155217697485
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective review of fall risk factors in the bone marrow transplant inpatient service

Abstract: Purpose The purpose of this study was to compare medications and potential risk factors between patients who experienced a fall during hospitalization compared to those who did not fall while admitted to the Blood and Marrow Transplant inpatient setting at The James Cancer Hospital. Secondary objectives included evaluation of transplant-related disease states and medications in the post-transplant setting that may lead to an increased risk of falls, post-fall variables, and number of tests ordered after a fall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…Risk factors for demographic characteristics of falls in patients with cancer were analyzed in this study. Four studies 4 , 9 , 17 , 18 were mentioned age as a factor and found that patients who developed falls were significantly older ( MD ​= ​3.74, 95% CI 0.72–6.77; I 2 ​= ​60%; P ​= ​0.02) ( Fig. 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Risk factors for demographic characteristics of falls in patients with cancer were analyzed in this study. Four studies 4 , 9 , 17 , 18 were mentioned age as a factor and found that patients who developed falls were significantly older ( MD ​= ​3.74, 95% CI 0.72–6.77; I 2 ​= ​60%; P ​= ​0.02) ( Fig. 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…1 ). Eventually, five studies 4 , 9 , 16 , 17 , 18 fulfilled the inclusion criteria and were included in the meta-analysis. Four studies 4 , 9 , 16 , 17 were case–control studies and one study 18 was a cohort study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This limits the generalizability to the target population of hospitalized adult patients with hematologic malignancy. Finally, the higher risk for falls among this population is a limitation to the generalizability of this study to other oncology patients [9]. Patients with hematologic malignancy undergo multiple chemotherapy treatments leading to a prolonged duration of severe cytopenias.…”
Section: Limitationsmentioning
confidence: 96%